Creating cyberspace in the Solar System: Future Human Image - Sergey Sukhonos (International Society of Philosophy and Cosmology, 2019)
In the article, the author considers the possibility of creating cyberspace in the Solar System. A new concept for the development of the Solar System using cybernetic systems and robots, which will be controlled by the new formation from Earth and partly with the help of inspection flights and commissioning, is proposed. This is a "cosmic civilization" considering the near space as a sphere of everyday self-realization. The evolutionary, social and technological aspects of the emergence and development of cyberspace are outlined. The evolutionary futility of space exploration using biological organisms is shown.